Preparation of a cross-linked cartilage acellular matrix-poly (caprolactone-ran-lactide-ran-glycolide) film and testing its feasibility as an anti-adhesive film - Park, Joon Yeong; Park, Seung Hun; Ju, Hyeon Jin; Ji, Yun Bae; Yun, Hee Woong; Min, Byoung Hyun; Kim, Moon Suk (Materials Science and Engineering C, 2020)
To protect unwanted tissue adhesions occurring after surgeries, we aimed to fabricate an anti-adhesive film using cartilage acellular matrix (CAM) with anti-vascular inhibition activity. Additionally, to fabricate anti-adhesive films with tunable swelling, mechanical, and biodegradation properties, a biodegradable polyester (PEP) with N-hydroxysuccinimide (NHS) in the chain end position was synthesized as a cross-linker. CAM/PEP (CP) films were prepared with various CAM: PEP ratios in the wide size with repeatable reproducibility, and then, cross-linked CP (Cx–CP) were obtained by the interpenetrating cross-linking reaction between the amine group on CAM and the NHS group on PEP cross-linkers under thermal treatment. The biodegradation, wettability, swelling, and mechanical properties of the prepared anti-adhesive Cx–CP films were controlled by varying the CAM:PEP ratio. The degradation half-life, contact angle, elastic moduli and toughness of Cx–CP films increased according to the increasing PEP content. Additionally, Cx–CP films significantly inhibits the attachment and proliferation of HUVECs. Cx–CP film prepared by varying the CAM:PEP ratio can be tailored to meet individual requirements for in vivo injured tissues. In animal experiments, anti-adhesive Cx–CP films implanted between the peritoneal wall and the cecum significantly suppressed tissue adhesion between them. Additionally, good adhesion effect observed at anti-adhesive film maintained for proper time period at injured tissues. Taken together, in this work, we successfully achieved strategy for the development of anti-adhesive barrier with tunable swelling, mechanical, and biodegradation properties.
Keywords: Acellular matrices; Animal experiments; Biodegradable polyesters; Crosslinking reaction; Inhibition activity; N-hydroxysuccinimide; Reproducibilities; Tissue adhesion; Adhesives; Animals; Caproates; Cartilage; Dioxanes; Feasibility Studies; Lactones; Reproducibility of Results; Anti-adhesive barrier; Cartilage acellular matrix; Cross-linking; Degradation; Polyester